2004
DOI: 10.1203/01.pdr.0000134251.45878.d5
|View full text |Cite
|
Sign up to set email alerts
|

Early Intestinal Bacterial Colonization and Necrotizing Enterocolitis in Premature Infants: The Putative Role of Clostridium

Abstract: Necrotizing enterocolitis (NEC) is among the most severe conditions that can affect preterm infants. Although the etiology of NEC remains unknown, initial bacterial colonization could play a pivotal role in the development of NEC. To further explore the putative relationship between pathogen microorganisms and NEC, we conducted a prospective casecontrol study in 12 preterm infants with a new approach based on molecular techniques. Over an inclusion period of 24 mo, 12 neonates of Ͻ34 wk gestational age admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 24 publications
11
153
2
3
Order By: Relevance
“…They found that, as compared with fecal samples from control neonates, samples from neonates who went on to develop NEC included many more kinds of bacteria that did not grow in culture. de la Cochetiere et al (23), using the molecular technique of temperature gradient gel electrophoresis, detected a band corresponding to Clostridium perfringens in three cases of neonates with NEC but in none of the controls. In our study, no specific DNA bands were correlated with the development of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…They found that, as compared with fecal samples from control neonates, samples from neonates who went on to develop NEC included many more kinds of bacteria that did not grow in culture. de la Cochetiere et al (23), using the molecular technique of temperature gradient gel electrophoresis, detected a band corresponding to Clostridium perfringens in three cases of neonates with NEC but in none of the controls. In our study, no specific DNA bands were correlated with the development of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the CS preterm pigs harbored assemblages of bacteria that were lower in density and diversity than those of VD pigs. The delayed colonization, as well as the less diverse and unstable assemblages typical of CS infants, is thought to increase susceptibility to pathogen overgrowth and disease (11,47); however, how bacterial diversity affects preterm intestines highly sensitive to bacterial colonization remains poorly defined. Yet, CS alone did not increase the incidence of NEC among the preterm pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact association and mechanisms between neonatal intestinal microbiota and NEC remain unclear, the interplay between them appears to be a dynamic one. As early as 2004, a temporal association between early colonization with Clostridium and later development of NEC was suggested (4). This temporal relationship is again illustrated by the observation of a differing intestinal microbiome 1 wk prior to the onset of NEC (5).…”
mentioning
confidence: 94%